The Wirecard lessons: A reform proposal for the supervision of securities markets in Europe - Jan Pieter Krahnen; Katja Langenbucher (Leibniz Institute for Financial Research SAFE, 2020)
The Wirecard scandal is a wake-up call alerting German politics to the importance of securities market integrity. The role of market supervision is to ensure the smooth functioning of capital markets and their integrity, creating trust among and acceptance by investors locally and globally. The existing patchwork of national supervisory practice in Europe is under discussion today, in the wake of Brexit that will end the role of London as a de-facto lead supervisor in stock and bond markets. A fundamental overhaul of a fragmented securities markets supervisory regime in Europe would offer the potential to lead to the establishment of an independent European Single Market Supervisor (ESMS). Endowed with strong enforcement powers, and supported by the existing national agencies, the ESMS would be entrusted with ensuring a uniform market standard as to transparency and other issues of market integrity across Europe. This would not rule out maintaining a variety of market organization structures at the national level. The ESMS would need executive powers in the world of markets (i.e. securities and trading), much like the SSM in the world of banking. To fill this new role, ESMS would have to be established as a new, independent institution, including an enormously scaled up staff if compared, e.g., to ESMA.
Keywords: 330; Wirecard; securities markets; market supervision